Decision Support System for Underprivileged Scholarship Recipients Using the Simple Additive Weighting (SAW) Method in XYZ University - Raymond Ramadhan, Yudhi; Alam, Syariful; Iman Hermanto, Teguh; Agus Sunandar, Muhamad; Arialdi, Miftahul (RISTEC : Research in Information Systems and Technology, 2023)
XYZ University as an educational institution that is responsible not only for academic quality, but also for equal access to higher education, has established various scholarship programs. However, a fair and transparent selection process for scholarship recipients is still a challenge. Unclear criteria, poorly defined weights, and an unstructured decision-making process can result in injustice for prospective students who should be eligible for financial aid. To overcome this problem, it is necessary to develop a Decision Support System (SPK) which can assist in the selection process for underprivileged scholarship recipients. The Simple Additive Weighting (SAW) method is a method that can be implemented because it is relatively easy to implement and can provide transparent and accountable results. Based on the calculation results, the student with the highest calculated score, namely 1,400, is a student who is recommended to be entitled to an educational scholarship.